The plane of the screen and space behind the screen: animation between modernism and realism / ПЛОСКОСТЬ ЭКРАНА И ПРОСТРАНСТВО ЗА ЭКРАНОМ: АНИМАЦИЯ МЕЖДУ МОДЕРНИЗМОМ И РЕАЛИЗМОМ - YATSYUK O.G. / ЯЦЮК О.Г.; MIKHAYLOV F.M. / МИХАЙЛОВ Ф.М. (Наука телевидения, 2017)
The article is devoted to animation art development. Having studied the history of plastic arts, authors come to a number of conclusions. Animation is a capacious and multidimensional phenomenon. Animation films (drawn, puppet or computer-generated), commercials, moving television prompts, laser shows are projected on some surface. Thus the screen is an element of composite construction and “works” differently. In flat animation its crative task is to limit the depth of the perceived image, to create a boundary background while in the volume movie the screen “is dissolved”. If images of flat animation are conditional and definitely connected with the screen, the volume graphics imitates reality, going out to the space behind the screen. With the emergence of 3D computer technologies work of animators significantly changed: there was no more need to trace angles of characters and shots taking into account perspective reductions and the position of lighting sources. All these problems began to be solved in virtual space. Besides, there was a possibility of computer editing and modeling of difficult movements that inevitably led to transformation of the genre. Degree of realism of computer space, unprecedented for animation, provoked discussion about the art value and expediency of naturalism in animation in professional community . However while today movies created in the programs Maya, Cinema 4D and so forth are shown mostly in main-stream cinema, in independent and festival animation the share of two-dimensional movies prevails. Why is flat animation so attractive? Laconic expressi-veness of a conditional image, significance. A laconic sign is perceived quicker and causes deep subjective feelings and associations. Therefore all movements, poses and mimics of characters of two-dimensional animation are always extremely simple, but very expressive. If the purpose of a work of art is to transmit information as fast as possible (both logical, and emotional), use of the flat, significant image solves this problem more effectively. Thus, despite powerful breakthrough of technologies of three-dimensional modeling and visualization, the spatial naturalism doesn’t dominate over modernist comprehension of the screen in animation. Intellectual and sensual comprehension of simple abstract images of a work of art directly depends on the level of development of active, complete, structural intelligent perception.